Overuse injury treatment: which is more appropriate between Swedish massage and deep tissue massage, especially for archery athletes - Prasetyo, Y.; Yachsie, B. T. P. W. B.; Suhasto, P.; Famelia, S. (Health, Sport, Rehabilitation, 2025)
Purpose To determine the influence of Swedish massage and deep tissue massage on the healing of the dominant muscles in archery players. Although the impact of massage cannot be completely isolated from injury, massage frequently reduces an athlete's performance.